DAMPAK KEBIJAKSANAAN PAJAK EKSPOR TERHADAP INVESTASI STUDI KASUS KAYU GERGAJIAN TROPIS (The impact or export tax policy on investment Case study : Tropical sawn timber - Setiasih Irawati (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
The objective of this study is to evaluate the impact of sawn timber export tax increase on investment in sawn timber industry. Sawn timber industry analyzed is limited to the sawmill belongs to the forest concession. The demond function for investment in sawn timber industry are evaluated as basis for impact estimation, using time series analysis, to estimate demand function for net investment (in(t)) in sawn timber industry. A distributed lag model was used.The result of the distributed lag model shows that the sawn timber export tax policy caused this industry adjust their investment in 1.3 years. The increase of sawn timber export tax rate to 78.3% at the and of 1989 had caused a decrease demand for net investment of sawn timber industry about Rp 222.970 billion (constant price 1983) and Rp 132,798 billion (constant price 1983) in 1990 and 1991, or about 50% respectively. The imposition of high sawn timber export tax rate as an effort to the development of wood finished product export, has not effective . sawn timber export tax policy hance have to be reviewed.International market for wood finished product, furniture in particular, is very competitive, consequently, for the success of finished product export, a strong marketing network, high quality product, and a better knowledge about market characteristic are needed in this regard the government support to wood finish product export should focuse on human resource development i.e providing skill labor in processing and marketing of wood finished product.